2013
DOI: 10.1084/jem.20130751
|View full text |Cite
|
Sign up to set email alerts
|

Gata2 is required for HSC generation and survival

Abstract: GATA2 function is essential for the generation of HSCs during the stage of endothelial-to-hematopoietic cell transition and thereafter for HSC survival

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
217
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 218 publications
(234 citation statements)
references
References 35 publications
5
217
1
3
Order By: Relevance
“…A single protein, GATA-2, governs hematopoietic stem cell (HSC) genesis from hemogenic endothelium in the aorta gonad mesonephros (AGM) region of the embryo and development of the hematopoietic system (de Pater et al, 2013; Tsai et al, 1994). GATA-2 also controls proliferation/survival of hematopoietic progenitors (Tsai and Orkin, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…A single protein, GATA-2, governs hematopoietic stem cell (HSC) genesis from hemogenic endothelium in the aorta gonad mesonephros (AGM) region of the embryo and development of the hematopoietic system (de Pater et al, 2013; Tsai et al, 1994). GATA-2 also controls proliferation/survival of hematopoietic progenitors (Tsai and Orkin, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Mouse embryo lacking Gata2 died at an early stage due to the severe anemia (Gao et al., 2013, Lim et al., 2012, Ling et al., 2004, Tsai et al., 1994). Notably, mouse HECs without Gata2 failed to produce long-term repopulating HSCs due to an impaired EHT (de Pater et al., 2013). We have also demonstrated that human embryonic stem cells (hESCs) with GATA2 deficiency exhibited a reduced EHT during blood differentiation (Huang et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…GATA-2 is expressed predominantly in hematopoietic stem/progenitor cells (HSPCs), mast cells, endothelial cells, and neurons (4)(5)(6)(7)(8). Through its actions to induce HSC generation (9,10) and to regulate HSPC function (11)(12)(13), GATA-2 mediates multilineage hematopoiesis. Mutations that alter the GATA2 coding region (14)(15)(16) or an essential cis element 9.5 kb downstream of the Gata2 1S promoter (ϩ9.5 site) (17,18) cause a primary immunodeficiency syndrome (MonoMAC) commonly associated with myelodysplastic syndrome (MDS) and acute myeloid leukemia (AML).…”
mentioning
confidence: 99%